Gender digital divide: digital skills among Malaysian secondary school - Ahmad, Nur 'Atikah; Mohd Ayub, Ahmad Fauzi; Md Khambari, Mas Nida (Human Resource Management Academic Research Society, 2019)
The Digital Divide is an important issue with serious consequences, individuals affected, society as well as threatens economy and productivity growth of a country. It was believed no longer exists in this 21st century era, amongst adolescents due to internet and smart devices penetration increment in Malaysia. Thus, survey conducted among 292 national secondary students from Hulu Langat district, chosen by using proportional random sampling to seek the possibility of digital divide existence by mean of digital skills between genders. There is no divide exist in digital devices ownership especially smartphones and home internet access. However, there was gender divide in digital skills in all dimensions except for information navigation skills even when gender is controlled. Male students had higher digital skills compared to female, whereby female only higher in information navigation skills. There was gender divide exist as well among urban secondary students, whereby urban male had highly digital skilled in computer operational, internet operational, social and creative skills, whilst urban female digitally skilled in information navigation. However, rural female suffered more in digital divide, whereby they were behind in digital skills level compared to rural male in the three dimensions. These findings indicate more efforts should be taken by the policy makers and authorities in enhancing students’ digital skills as well as bridging the digital divide in accommodating them well into today’s informative world.